2020
DOI: 10.21203/rs.3.rs-96828/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Bovine Neutrophil Extracellular Traps Induced by Histamine

Abstract: BackgroundHistamine plays an central role in many allergic diseases including allergic asthma and allergic rhinitis, and is also involved in bovine laminitis through regulating immune responses. Neutrophil extracellular traps (NETs) formation is a novel effector mechanism of neutrophils to defend against various stimuli. In the present study, we aimed to investigate the role of histamine on bovine NET formation and examined its fundamental molecular mechanisms. ResultsFirstly, the effects of histamine on neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that cow neutrophils release NETs in response to the free-living soil nematode Caenorhabditis elegans , that NET production may be a conserved mechanism against a broad range of nematodes. The cattle stomach worm O. ostertagi -induced NET formation by a ROS-independent and NADPH oxidase dependent pathway [ 120 ]. Fascioliasis is a zoonotic disease caused by infection with the trematode Fasciola hepatica , resulting in hepatitis in humans and livestock.…”
Section: Mammalian Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…Studies have demonstrated that cow neutrophils release NETs in response to the free-living soil nematode Caenorhabditis elegans , that NET production may be a conserved mechanism against a broad range of nematodes. The cattle stomach worm O. ostertagi -induced NET formation by a ROS-independent and NADPH oxidase dependent pathway [ 120 ]. Fascioliasis is a zoonotic disease caused by infection with the trematode Fasciola hepatica , resulting in hepatitis in humans and livestock.…”
Section: Mammalian Neutrophil Extracellular Trapsmentioning
confidence: 99%